Adaptability of grocery by phone in Iloilo City - Clavel, June Anthony; Otico, Annalene Mae; Pesando, Ophelia; Robles, Roselle; Tuusan, Annalyn
The primary objective of the study was to determine the adaptability of grocery by phone here in Iloilo City. In attaining the objective, the researchers employed random sampling in selecting respondents and data gathering techniques in the form of survey questionnaire. The study disclosed the following : 1) That personal and demographic factors have no significant relation as to the consumers willingness to avail the services of grocery by phone ; 2) That behavioral and buying practices of the consumers have no significant relation as to their willingness to avail the service of grocery by phone. Though those factors aforementioned above have no significant relations as to the consumers willingness in availing the services of grocery by phone, this new scheme is adaptable in Iloilo City especially to the families whose income bracket belong from middle to upper. The researchers of this study recommend for its further study and in-depth treatment.